A novel drug-like water-soluble small molecule Focal Adhesion Kinase (FAK) activator promotes intestinal mucosal healing - Qinggang Wang; Ricardo Gallardo-Macias; Emilie E. Vomhof-DeKrey; Rashmi Gupta; Svetlana A. Golovko; Mikhail Y. Golovko; Sema Oncel; Vadim J. Gurvich; Marc D. Basson (Elsevier, 2023)
Non-steroidal anti-inflammatory drugs (NSAIDs) injure the proximal and distal gut by different mechanisms. While many drugs reduce gastrointestinal injury, no drug directly stimulates mucosal wound healing. Focal adhesion kinase (FAK), a non-receptor tyrosine kinase, induces epithelial sheet migration.We synthesized and evaluated a water-soluble FAK-activating small molecule, M64HCl, with drug-like properties. Monolayer wound closure and Western blots measured migration and FAK phosphorylation in Caco-2 ​cells, in vitro kinase assays established FAK activation, and pharmacologic tests assessed drug-like properties. 30 ​mg/kg/day M64HCl was administered in two murine small intestine injury models for 4 days.M64HCl (0.1-1000 ​nM) dose-dependently increased Caco-2 FAK-Tyr 397 phosphorylation, without activating Pyk2 and accelerated Caco-2 monolayer wound closure. M64HCl dose-responsively activates the FAK kinase domain vs. the non-salt M64, increasing the Vmax of ATP-binding. Pharmacologic tests suggested M64HCl has drug-like properties and is enterally absorbed. M64HCl 25 ​mg/kg/day continuous infusion promoted healing of ischemic jejunal ulcers and indomethacin-induced small intestinal injury in C57Bl/6 mice. M64HCl-treated mice exhibited smaller ulcers 4 days after ischemic ulcer induction or indomethacin injury. Renal histology and plasma creatinine were normal. Mild hepatic inflammatory changes and ALT elevation were similar among M64HCl-treated mice and controls. M64HCl was concentrated in kidney and gastrointestinal mucosa and functional nephrectomy studies suggested predominantly urinary excretion. Little toxicity was observed in vitro or in single-dose mouse toxicity studies until >1000x higher than effective concentrations. M64HCl, a water-soluble FAK activator, promotes epithelial restitution and intestinal mucosal healing and may be useful to treat gut mucosal injury.